A case series of very slow atrioventricular nodal reentrant tachycardia resembling junctional tachycardia. (12th April 2022) - Higuchi, Koji; Higuchi, Satoshi; Baranowski, Bryan; Wazni, Oussama; Scheinman, Melvin M.; Tchou, Patrick
Abstract: Introduction: The surface electrocardiography of typical atrioventricular nodal reentrant tachycardia (AVNRT) shows simultaneous ventricular‐atrial (RP) activation with pseudo R′ in V1 and typical heart rates ranging from 150 to 220/min. Slower rates are suspicious for junctional tachycardia (JT). However, occasionally we encounter typical AVNRT with slow ventricular rates. We describe a series of typical AVNRT cases with heart rates under 110/min. Methods: A total of 1972 patients with AVNRT who underwent slow pathway ablation were analyzed. Typical AVNRT was diagnosed when; (1) evidence of dual atrioventricular nodal conduction, (2) tachycardia initiation by atrial drive train with atrial‐His‐atrial response, (3) short septal ventriculoatrial time, and (4) ventricular‐atrial‐ventricular (V‐A‐V) response to ventricular overdrive (VOD) pacing with corrected post pacing interval‐tachycardia cycle length (cPPI‐TCL) > 110 ms. JT was excluded by either termination or advancement of tachycardia by atrial extrastimuli (AES) or atrial overdrive (AOD) pacing. Results: We found 11 patients (age 20−78 years old, six female) who met the above‐mentioned criteria. The TCL ranged from 560 to 782 ms. Except for one patient showing tachycardia termination, all patients demonstrated a V‐A‐V response and cPPI‐TCL over 110 ms with VOD. AES or AOD pacing successfully excluded JT by either advancing the tachycardia in 10 patients or by tachycardia termination in one patient. Slow pathway was successfully ablated, and tachycardia was not inducible in all patients. Conclusions: This case series describes patients with typical AVNRT with slow ventricular rate (less than 110/min) who may mimic JT. We emphasize the importance of using pacing maneuvers to exclude JT.